Status of Axillary Staging in Patients with Breast Cancer and Its Impact on the Management of Patients - alireza, javadinia; Porouhan, Pejman; Abbaspour, Alaleh; Fazilat-Panah, Danial; PeyroShabany, Babak (Reports of Radiotherapy and Oncology, 2024)
Background: Breast cancer is most common in women, and symptoms and treatment depend on ethnicity, screening, and drug availability. The current standard for breast surgery is breast-conserving surgery (BCS) and sentinel lymph node biopsy (SLNB). However, performing axillary lymph node dissection (ALND) and the number of lymph nodes examined to determine the N stage has been insufficient in many patients, with a maximum of 10 lymph nodes assessed in patients undergoing ALND. This limitation leads to inadequate estimation and ultimately affects treatment choices. Objectives: This study examined the status of axillary staging in patients with breast cancer and its impact on management. Methods: This retrospective longitudinal cohort study included 272 breast cancer patients at Sabzevar University of Medical Sciences, Sabzevar, Iran, from 2015 to 2019. Data regarding laterality, mass location, histology, grade, in situ status, lymphovascular invasion, perineural invasion, necrosis, and AJCC TNM staging were collected. Results: Most patients were at stage two (54.1%), and the median size of the primary breast tumor was 1.3 cm (range 1 - 14 cm, mean 3.7 ± 2.1 cm). The median number of dissected lymph nodes was 8 (range 1 - 37, mean 8.3 ± 5.8); however, no lymph nodes were examined pathologically in 23% (n = 63) of patients despite undergoing ALND. Additionally, in 38.2% of patients undergoing ALND, less than 10 lymph nodes were examined, which is considered inadequate for accurate axillary staging. Conclusions: The rates of inadequate lymph node staging were considerable in our patients, resulting in overtreatment.